Polymorphisms of the Beta Fibrinogen Gene and Plasma Fibrinogen Concentration in Caucasian and Japanese Population Samples - Iso, Hiroyasu; Folsom, Aaron R; Winkelmann, John C; Koike, Kazuko; Harada, Shoji; Greenberg, Beryl; Sato, Shinichi; Shimamoto, Takashi; lida, Minoru; Komachi, Yoshio (Thrombosis and Haemostasis, 1995)
We reported previously that plasma fibrinogen was significantly higher in U.S. Caucasians than in Japanese, which may contribute to the higher mortality rate of coronary heart disease in the United States than in Japan. To examine the contribution of genetic variations to the race difference in plasma fibrinogen levels, restriction fragment length polymorphisms (RFLPs) of the beta fibrinogen gene were examined in 293 nonsmoking Caucasians and Japanese men and women aged 47-69 years. Three RFLPs were detected by digestion of genomic DNA using the BclI restriction enzyme, polymerase chain reaction (PCR) products using HaeIII and HindIII. The alleles B2 (4.2 kb, BclI digestion), H2 (957 b, HaeIII) and Hd2 (465 b, HindIII) were associated with higher fibrinogen concentrations in previous studies. Because of a strong linkage disequilibrium between HaeIII and HindIII polymorphisms, the data of HindIII was presented. The frequency of the B2 allele was 22% (95% Cl: 17-27%) for Caucasians and 13% (10-17%) for Japanese (the difference: p <0.01). The respective frequency of the Hd2 allele was 26% (21-31%) and 12% (8-16%) (p <0.001). After controlling for age, body mass index, alcohol intake, triglycerides, fish intake, and for women, menopausal status and hormone replacement therapy, the adjusted mean fibrinogen level among Caucasians was 289 mg/dl for genotype B1B1 and 301 mg/dl for genotype B1B2 or B2B2 combined (p = 0.18), and 285 mg/dl for Hd1Hd1 and 306 mg/dl for Hd1Hd2 or Hd2Hd2 combined (p = 0.03). The respective mean values among Japanese were 251 mg/dl for B1B1 and 257 mg/dl for B1B2 or B2B2 combined (p = 0.37), 248 mg/dl for Hd1Hd1 and 259 mg/dl for Hd1Hd2 or Hd2Hd2 combined (p = 0.16). These polymorphisms had a similar effect on plasma fibrinogen concentrations for both men and women. The results suggest that a genetic difference may partly explain the higher plasma fibrinogen in Caucasians than in Japanese.